Challenges of creating alliances across borders: midterm reflections from the Alliance for African partnership. Issue 2 (4th May 2019) - Minde, Isaac; Monson, Jamie
ABSTRACT: This paper seeks to share cross-border (geographic, disciplinary and cultural) challenges in the ethical design, establishment, implementation, and evaluation of the performance of alliances and partnerships. The paper reviews the Alliance for African Partnership's two-year experience stressing lessons learned and shows how it has benefitted philosophically on the subject from recent linkage with the International Development Ethics Association. The paper concludes by emphasizing the need to be patient as alliances and partnerships go through the learning curve before maturity in embracing the ethical values that come to bear. Strategies for nurturing, upkeep, and sustainability of these values are outlined.